Analysis of Phase and Energy Band Gap Width of Corncob Carbon-PEG 4000 - Kusuma Wardhani Mas'udah; Darminto Darminto (JPSE (Journal of Physical Science and Engineering), 2022)
This study aims to identify and analyze the band gap width of the carbon phase produced from corncobs mixed with PEG-4000 to see the surface area of the corncob carbon phase. First, the characterization test was carried out using Scanning Electron Microscope Energy-Dispersive X-ray (SEM-EDX) spectroscopy to determine the morphology and Ultraviolet–Visible (UV-Vis) spectroscopy to determine the band gap width of corncob carbon. Then, adding Polyethylene Glycol (PEG) 4000 at a specific concentration to develop the potential of corncob carbon. Finally, the corncob-PEG 4000 carbon reduction process was sifted through and tested by UV-Vis spectroscopy, and the energy gap value was 0.954 eV.DOI: 10.17977/um024v7i22022p142